The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/photonics10070834
|View full text |Cite
|
Sign up to set email alerts
|

Success Rate of Direct Pulp Capping with Conventional Procedures Using Ca (OH)2 and Bioactive Tricalcium Silicate Paste vs. Laser-Assisted Procedures (Diode 980 nm, CO2, and Er: YAG)

Abstract: Direct pulp capping (DPC) is reliable in pulp exposure management. Objective: This study aimed to assess the success rate of DPC materials and different laser protocols. The included procedures were CO2 laser (n = 1147), Er: YAG laser (n = 69), and 980 nm diode laser (n = 124), on the one hand, and Ca (OH)2 (n = 376) and bioactive tricalcium silicate paste, on the other (n = 279). Materials and methods: Data from 1995 DPC cases were included. For laser groups, irradiation was used to coagulate the pulp exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
0
0
Order By: Relevance
“…Research has shown that the type of pulp capping material can affect the outcome of VPT. 26,27 While calcium hydroxide (CH) was previously the standard for DPC, it has become less popular due to its lack of sealing ability, degradation over time and inefficient biocompatibility. Recent studies have demonstrated better clinical outcomes with the use of mineral trioxide aggregates (MTA) or Biodentine in VPT.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the type of pulp capping material can affect the outcome of VPT. 26,27 While calcium hydroxide (CH) was previously the standard for DPC, it has become less popular due to its lack of sealing ability, degradation over time and inefficient biocompatibility. Recent studies have demonstrated better clinical outcomes with the use of mineral trioxide aggregates (MTA) or Biodentine in VPT.…”
Section: Discussionmentioning
confidence: 99%